Statins: a role in breast cancer therapy?. (9th July 2018) - Borgquist, S.; Bjarnadottir, O.; Kimbung, S.; Ahern, T. P.
Abstract: Statin drugs have been used for more than two decades to treat hypercholesterolemia and as cardio‐preventive drugs, resulting in a marked decrease in cardiovascular morbidity and mortality worldwide. Statins halt hepatic cholesterol biosynthesis by inhibiting the rate‐limiting enzyme in the mevalonate pathway, hydroxymethylglutaryl‐coenzyme A reductase (HMGCR). The mevalonate pathway regulates a host of biochemical processes in addition to cholesterol production. Attenuation of these pathways is likely responsible for the myriad benefits of statin therapy beyond cholesterol reduction – the so‐called pleiotropic effects of statins. Chief amongst these purported effects is anti‐cancer activity. A considerable body of preclinical, epidemiologic and clinical evidence shows that statins impair proliferation of breast cancer cells and reduce the risk of breast cancer recurrence. Potential mechanisms for this effect have been explored in laboratory models, but remain poorly understood and require further investigation. The number of clinical trials assessing the putative clinical benefit of statins in breast cancer is increasing. Currently, a total of 30 breast cancer/statin trials are listed at the global trial identifier website clinicaltrials.gov. Given the compelling evidence from performed trials in a variety of clinical settings, there have been calls for a clinical trial of statins in the adjuvant breast cancer setting. It would be imperative for such a trial to incorporate tumour biomarkers predictive of statin response in its design and analysis plan. Ongoing translational clinical trials aimed at biomarker discovery will help identify, which breast cancer patients are most likely to benefit from adjuvant statin therapy, and will add valuable clinical knowledge to the field.